Penile Prosthesis Implantation in Patients with a History of Total Phallic Construction. (8th December 2015) - Zuckerman, Jack M.; Smentkowski, Katherine; Gilbert, David; Storme, Oscar; Jordan, Gerald; Virasoro, Ramon; Tonkin, Jeremy; McCammon, Kurt
Abstract: Introduction: Outcomes following penile prosthesis implantation in patients with a history of total phallic construction are not well described. Aim: The aim of this study was to evaluate outcomes following neophallus penile prosthesis placement. Methods: Retrospective review penile prosthesis placement in patients with prior total phallic construction. GORE‐TEX® (Gore Medical, Flagstaff, AZ) sleeve neotunica construction was utilized in all patients. Main Outcome Measure: Success defined as patient sexual activity with a functioning prosthesis. Results: Thirty‐one patients underwent neophallic prosthesis implantation at a mean 35.6 years of age. Prosthesis placement occurred at an average 56.3 months following phallic construction and follow‐up was a mean of 59.7 months. Malleable prostheses were placed in 21 patients and inflatable in 10; implants were bilateral in 94%. Six percent experienced operative complications including a bladder injury (1) and phallic flap arterial injury (1). Postoperative complications occurred in 23% at a median 5.5 months following placement. Five prostheses were explanted secondary to infection or erosion and two additional required revisions. Of the explanted prosthesis two were later replaced without further complication. Eighty‐one percent of patients were sexually active following prosthesis placement. Conclusions: Penile prosthesis placement is possible in patients with prior penile reconstruction/phallic construction. Although complications rates appear to be elevated in this population compared with historic controls of normal anatomic men, the majority of patients in this series were sexually active following prosthesis placement. This demonstrates the utility of prosthesis implantation in these difficult patients.Zuckerman JM, Smentkowski K, Gilbert D, Storme O, Jordan G, Virasoro R, Tonkin J, and McCammon K. Penile prosthesis implantation in patients with a history of total phallic construction. J Sex Med 2015;12:2485–2491.